Unit labor costs and manufacturing sector performance in Africa - Karmen Naidoo; Léonce Ndikumana (University of Massachusetts, Department of Economics, 2020)
Several studies have highlighted that African manufacturing wages are higher than comparator countries at similar levels of development, which contributes to the continent's lower levels of manufacturing competitiveness. This paper derives unit labor costs - average wages relative to productivity - for two-digit manufacturing sectors across a wide range of developed and developing countries over the 1990-2015 period. We benchmark the unit labor costs to China and estimate the impact of relative unit labor costs on manufacturing sector value added, employment, investment and exports. We find that relative unit labor costs have a smaller effect on manufacturing performance in Africa relative to other developing regions. Further, we find that for Africa, the level and growth of labor productivity have a quantitatively stronger and more robust effect on manufacturing performance than the level and growth of real wages. The results have important implications for industrial policy in African countries.
Keywords: O14; L60; E24; J30; 330; labor costs; productivity; manufacturing; exports; investment; Africa; China